2011
DOI: 10.1093/eurheartj/ehr291
|View full text |Cite
|
Sign up to set email alerts
|

Primary angioplasty in acute myocardial infarction with right bundle branch block: should new onset right bundle branch block be added to future guidelines as an indication for reperfusion therapy?

Abstract: AimsThe current guidelines recommend reperfusion therapy in acute myocardial infarction (AMI) with ST-segment elevation or left bundle branch block (LBBB). Surprisingly, the right bundle branch block (RBBB) is not listed as an indication for reperfusion therapy. This study analysed patients with AMI presenting with RBBB [with or without left anterior hemiblock (LAH) or left posterior hemiblock (LPH)] and compared them with those presenting with LBBB or with other electrocardiographic (ECG) patterns. The aim wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
85
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(98 citation statements)
references
References 24 publications
8
85
1
4
Order By: Relevance
“…Previous reports about AMI combined with new onset RBBB showed that the incidence of new RBBB in AMI was 4-18%. The research results showed that the incidence of new RBBB in AMI patients in the first 12 h was 6.32%, slightly higher than the incidence in the reports of Wagner et al (17) and Widimsky et al (18), and also higher than the incidence of new LBBB in this research. There was no obvious difference in the peak level of CK-MB, the level of heart function, the incidence of in-hospital MACE and in-hospital mortality between RBBB group and LBBB group; but all indexes in the former two groups were higher than those in the non-BBB group.…”
Section: Discussioncontrasting
confidence: 67%
“…Previous reports about AMI combined with new onset RBBB showed that the incidence of new RBBB in AMI was 4-18%. The research results showed that the incidence of new RBBB in AMI patients in the first 12 h was 6.32%, slightly higher than the incidence in the reports of Wagner et al (17) and Widimsky et al (18), and also higher than the incidence of new LBBB in this research. There was no obvious difference in the peak level of CK-MB, the level of heart function, the incidence of in-hospital MACE and in-hospital mortality between RBBB group and LBBB group; but all indexes in the former two groups were higher than those in the non-BBB group.…”
Section: Discussioncontrasting
confidence: 67%
“…12,13 This has recently been shown to be the case also in the PCI era. 7 Current guidelines focus on the association between left BBB and anterior wall infarction. However, using GUSTO-1 and TAMI-19 data, Newby et al 14 demonstrated an even stronger association between right BBB and anterior wall infarction.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4] The mortality risk also applies to patients with right bundle branch block myocardial infarction (BBBMI) since these patients often have significant coronary artery disease. [5][6][7] Only a minority of patients with BBBMI is treated with reperfusion therapy as recommended by the guidelines, 8 most likely because the diagnosis of new-onset BBB in the Diagnosis and outcome in a prehospital cohort of patients with bundle branch block and suspected acute myocardial infarction acute phase of myocardial infarction is based solely on an ECG and the clinical condition of the patients, with limited access to previous patient records. 9 The purpose of the present study was to determine the prevalence of acute myocardial infarction (AMI) with or without BBB and the associated outcome in an unselected cohort of patients with suspected AMI, diagnosed pre-hospital by Telemidical ECG transmission.…”
Section: Introductionmentioning
confidence: 99%
“…Anterior STEMI associated with RBBB, particularly new RBBB, has bad prognosis and is often due to proximal left anterior descending (LAD) occlusion causing extensive infarction of the interventricular septum where the right bundle traverses [12]. In a retrospective analysis of 6742 consecutive patients with acute MI (including both STEMI and non-STEMI) undergoing angiography [13], Widimsky et al reported that even in large infarcts caused by left main or proximal LAD coronary occlusions RBBB may occur without the typical ST elevation required for diagnosing anterior STEMI. Indeed, they titled their paper as "Primary angioplasty in acute myocardial infarction with right bundle branch block: should new onset right bundle branch block be added to future guidelines as an indication for reperfusion therapy?"…”
Section: The Standard Ecg Leads Do Not Cover Well the Posterior (Infementioning
confidence: 99%